2021
DOI: 10.1093/ijnp/pyab021
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Palmitate Paliperidone Long-Acting Injectable Formulations’ Use in Schizophrenia Spectrum Disorders: A Retrospective Cohort Study from the First Episode Psychosis Intervention Program (CRUPEP)

Abstract: Background Long-acting injectable antipsychotics (LAIs) may be a suitable therapeutic option for those patients in earlier stages of psychosis to avoid relapses and disease progression. Despite that, there is a lack of evidence in the literature regarding the use of LAIs in this profile of patients. Methods This is a retrospective cohort analysis to assess the efficacy, tolerability, and pattern of use of palmitate paliperido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, a recent study evaluated the role of PP1M, PP3M versus oral paliperidone and risperidone in the first episode of psychosis. 57 Patients in the PP3M group achieved significant improvements compared to oral treatments in overall clinical symptom severity and saw a substantial improvement in the main domains of personal and social functioning after 1 year. Also this study demonstrated that patients treated with PP3M associated a lower concomitant use of benzodiazepines.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, a recent study evaluated the role of PP1M, PP3M versus oral paliperidone and risperidone in the first episode of psychosis. 57 Patients in the PP3M group achieved significant improvements compared to oral treatments in overall clinical symptom severity and saw a substantial improvement in the main domains of personal and social functioning after 1 year. Also this study demonstrated that patients treated with PP3M associated a lower concomitant use of benzodiazepines.…”
Section: Resultsmentioning
confidence: 86%
“…Also this study demonstrated that patients treated with PP3M associated a lower concomitant use of benzodiazepines. 57 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation